2017
DOI: 10.1108/cg-11-2015-0150
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between corporate governance, corruption and forward-looking information disclosure: a comparative study

Abstract: Purpose This paper aims to examine the relationship between corporate governance, corruption and disclosure of forward-looking information in listed firms in two African countries, Botswana and Ghana. Design/methodology/approach The study uses 174 firm-year observations between the period of 2011-2013 for listed firms in the two countries. Each annual report was individually examined and coded to obtain the disclosure of forward-looking information index. Descriptive analysis was performed to provide the bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
5
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 74 publications
(52 reference statements)
4
50
5
3
Order By: Relevance
“…With regard to the control variables, company size had a positive influence on anti-corruption practices. The result is consistent with the assumption that larger companies are exposed to public scrutiny, which leads to greater voluntary disclosure (Agyei-Mensah, 2017;Frías-Aceituno et al, 2014). The recent Brazilian political and business context justifies large companies' attitude on matters of fight against corruption, with a view to increasing legitimacy in the market.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…With regard to the control variables, company size had a positive influence on anti-corruption practices. The result is consistent with the assumption that larger companies are exposed to public scrutiny, which leads to greater voluntary disclosure (Agyei-Mensah, 2017;Frías-Aceituno et al, 2014). The recent Brazilian political and business context justifies large companies' attitude on matters of fight against corruption, with a view to increasing legitimacy in the market.…”
Section: Resultssupporting
confidence: 81%
“…Previous findings also revealed that BOD independence (Agyei-Mensah, 2017;Donnelly & Mulcahy, 2008) In addition to international efforts and legal requirements at the country level, accounting and auditing standards based on CG principles culminate in the quality and integrity of organizations that mitigate and curb corrupt practices. Accounting is an essential transparency mechanism whose role is to demonstrate the company's operations, reflected by reality in a precise, comparable manner, and, in turn, the role of auditing is to guarantee the accuracy of that information to its users (Owolabi, 2011).…”
Section: Cg and Csr In Anti-corruption Practicesmentioning
confidence: 99%
“…;and Wilson (2008);Jalilian et.al., (2006);Pellegrini & Gerlagh, (2004); and Mauro (1995) that a government with poor law enforcement causes corruption. While the results of the study are not in line with Agyei & Mensah (2017);Habibullah et.al. 2016;Caiden (2013); Rose-Ackerman et.al.…”
Section: The Effect Of Good Governance On the Causes Of Corruptioncontrasting
confidence: 93%
“…In that regard, while firms are not responsible for solving all societal issues, especially those that they have no input in causing, they should address the problems that they create, and especially the socioenvironmental concerns of their business operations (Kanter, 2011). This is especially important in developing countries, such as Nigeria, marred by weak regulation and corruption (Okike et al, 2015;Agyei-Mensah, 2017;. It is from this perspective that we explore how CSR can represent a smarter, voluntary, and complementary (and in some cases as an alternative) governance instrument to the hitherto existing governance mechanisms of corporate externalities.…”
Section: The Pursuit Of Shareholder Value and The Governance Of Its Cmentioning
confidence: 99%